Bibliometric analysis of learning mathematics studies from Indonesian authors - Supriyadi, Edi; Dahlan, Jarnawi Afgani; Dasari, Dadan; Darhim, Darhim; Sugiarni, Rani (UNIVERSITAS NEGERI MALANG, 2022)
The concept of learning mathematics in schools has evolved to mean learning to participate in mathematical practices. In the 20th century, math education research developed, but each key issue and approach offers many questions. For the purpose of this inquiry, the Bibliometrics Analysis was carried out. When performing research on bibliographic material and carrying out citation analysis of each article published in scientific journals and other types of scientific literature, researchers could find it beneficial to use bibliometric analysis. This is a quantitative descriptive research. Researchers want to investigate the evolution of mathematics learning research outcomes in Indonesia, the distribution pattern of publications based on research affiliations, research themes, and scientific journals in Scopus. This study presents findings that are exploratory in nature from research on mathematics education in Indonesia. This study investigates the central body of scientific work in the subject of mathematics learning with the goal of providing information to educators, lecturers, and institutions of higher education about the current state of research trends in the field of mathematics learning. The data indicate that there has been less study conducted on mathematical education during the past two years. At the present time, the Universitas Pendidikan Indonesia is the association with the most significant influence. When it comes to publications, the Journal of Physics: The Conference Series has more mathematics learning research articles than any other Scopus-indexed journal.